EXPLORING THE INFLUENCE OF SELF-EFFICACY TO UNDERGRADUATE STUDENTS' VOCABULARY MASTERY - Indri Gisella; M Mulyadi (Universitas Tridinanti Palembang, 2021)
Self-efficacy has become one of the important factor in learning, especially learning language, self-efficacy has brought essential effect to learners themselves that could influence the outcome of study development well. Vocabulary carries essential role in mastering a language, so therefore, it is important to find out the influence between both self-efficacy and vocabulary mastery. The objective of this research was to find out the influence of self-efficacy to undergraduate students' vocabulary mastery. The correlation research design was applied in this research. The population of this research was 54 seventh semester students of English education study program at University of PGRI Palembang in academic year 2020/2021. As the sample of the research, 24 seventh semester students of PGRI University of Palembang were selected through purposive sampling, the judgment of selecting the sample was consideration of students’ vocabulary score and the discussion between researcher and the lecturer. The data were collected by using questionnaire and test, they are self-efficacy questionnaire and vocabulary test. The result of the test and questionnaire were analyzed by using simple linear regression analysis. The result analysis showed that the Sig value of simple linear regression was 0.01 which is lower than α 0.05. Based on the regression analysis result, there was a significant influence of self-efficacy to undergraduate students' vocabulary mastery at University of PGRI Palembang. Keywords: self-efficacy, vocabulary mastery